EVALUATING THE EFFECTIVENESS OF DIGITAL COMMUNICATION IN PUBLIC HEALTH CAMPAIGNS - Annafiatuzakiah; Winda Chelsea Meisari (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This research aims to evaluate the effectiveness of digital communication in public health campaigns. Using digital analytics tools, this evaluation focuses on understanding the reception of health messages by audiences and the behavioural changes that occur as a result. The review in this study used the literature method. The results showed that continuous analysis and strategy adjustments based on the evaluation can improve the efficiency and impact of digital health campaigns. The conclusion of this study confirms the importance of thorough evaluation to ensure that health messages are not only well delivered, but also able to positively change people's behaviour, ultimately contributing to the overall improvement of people's well-being and health.